2021
DOI: 10.1002/ansa.202000167
|View full text |Cite
|
Sign up to set email alerts
|

Targeted NMR‐based serum metabolic profiling of serine, glycine and methionine in acute‐on‐chronic liver failure patients: Possible insights into mitochondrial dysfunction

Abstract: Background A recent study based on blood metabolomics analysis revealed inflammation‐associated mitochondrial dysfunction as a potential mechanism underlying acute‐on‐chronic liver failure (ACLF) in cirrhotic patients. Serine, glycine, and methionine serve to maintain a healthy immune system and adequately sustain mitochondrial functionality in hepatocytes for regulating redox homeostasis through the production of antioxidant glutathione (GSH). Based on this, we hypothesized that the circulatory levels of seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…Figure A shows the stack plot of the 1D 1 H CPMG NMR spectra recorded on serum samples obtained from EM and NC subjects. The present study involves concentration profiling of proline and glutamine in the serum samples of EM patients and NC subjects following a targeted 1 H NMR based metabolomics approach as described previously. , For this, first we have identified the NMR signals corresponding to proline and glutamine and assigned by following a chemical shift and peak pattern matching procedure employing the 800 MHz spectral database of metabolites in the NMR suite of CHENOMX software; the selected spectral regions are shown in Figure B (for glutamine) and Figure C (for proline). To minimize the experimental/methodological deviations, the proline and glutamine concentrations were explicitly measured using formate as an internal reference (explicit details are described in the Materials and Method).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure A shows the stack plot of the 1D 1 H CPMG NMR spectra recorded on serum samples obtained from EM and NC subjects. The present study involves concentration profiling of proline and glutamine in the serum samples of EM patients and NC subjects following a targeted 1 H NMR based metabolomics approach as described previously. , For this, first we have identified the NMR signals corresponding to proline and glutamine and assigned by following a chemical shift and peak pattern matching procedure employing the 800 MHz spectral database of metabolites in the NMR suite of CHENOMX software; the selected spectral regions are shown in Figure B (for glutamine) and Figure C (for proline). To minimize the experimental/methodological deviations, the proline and glutamine concentrations were explicitly measured using formate as an internal reference (explicit details are described in the Materials and Method).…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, the spectrum was opened in the PROCESSOR module of CHENOMX NMR Suite 8.6 software and further better corrected for baseline and calibrated with respect to the formate peak at 8.43 ppm. For concentration profiling, formate was also used as an internal reference and the concentration was set to 10 μM (i.e., nearly close to the detection limit of metabolites in the CPMG NMR spectra of serum samples recorded at 800 MHz NMR spectrometer). , The advantage of selecting formate as an internal reference has already been demonstrated in previous methodological studies , including recent metabolomics studies from our lab. , Studies have shown that, unlike TSP, formate does not interact with serum proteins/macromolecules and, therefore, has legitimate potential to serve as an internal reference for quantitative profiling of metabolites from blood serum (and eventually other biological fluids) in normal and diseased conditions not involving disorders of endogenous formate metabolism. After data processing, the spectrum was imported to the PROFILER-Module of CHENOMX and the concentrations of selected metabolites (i.e., proline and glutamine) were estimated in all the serum samples of EM patients and NC subjects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another NMR‐based targeted metabolomics study by Arya et al 6 investigated the circulatory levels of serine and glycine in the sera of 40 ACLF patients and 49 normal controls (NC) subject using 1D 1H CPMG NMR spectra that provided insights into the potential mechanisms of acute‐on‐Chronic liver failure (ACLF) in cirrhotic patients. The authors showed that the circulating levels of serine and glycine were significantly decreased in ACLF patients (Ser = 23.06 ± 1.67 and Gly = 83.11 ± 7.52) compared to NC subjects (Ser = 55.61 ± 2.28 and Gly = 156.9 ± 7.16) with p ‐value < 0.0001, indicative of depressed immune system and mitochondrial dysfunction.…”
mentioning
confidence: 99%